Are older adults' home exposures to secondhand smoking during earlier life stages associated with current health status and life satisfaction in China? A multilevel approach. Issue 3 (3rd August 2020) - Lee, Yen-Han; Chang, Yen-Chang; Lee, Yi-Ting Hana; Liu, Ching-Ti; Shelley, Mack
Abstract: Secondhand smoking (SHS) has become a critical challenge in Chinese society, and progress on SHS prevention remains unknown. There is little knowledge targeting Chinese older adults generally to investigate the associations between SHS exposure experiences during earlier life stages and health-related measurements. Using cross-sectional data from a nationally representative data set, the 2014 wave of the Chinese Longitudinal Healthy Longevity Survey ( n = 4, 414), multilevel logistic regression models with random effects for Chinese provinces were used for analyses. Two health-related measurements included self-reported health status and life satisfaction. All regression models included the same set of predictors and covariates with socioeconomic factors and basic biological information. Approximately 40% and 47% of older adults reported SHS exposure in childhood and in younger adulthood at home, respectively. Older adults with SHS exposure in childhood had lower odds of reporting better health status, compared with those who did not have such exposure (adjusted odds ratio [AOR] = 0.69, 95% CI [0.55, 0.86], p < .01). However, life satisfaction was not associated with any SHS exposure experiences. Policy makers and public health practitioners should continue to investigate the long-term effect of SHS exposure on human health, including older adults. Policy regarding SHS prevention should be enhanced.